Framing analyses of mainstream and independent media: frame preferences before and after the Malaysian 15th general election - Xin Yi, Yong; Waheed, Moniza; Jen Sern, Tham; Mohd Zawawi, Julia Wirza (Human Resource Management Academic Research Society, 2024)
The recent changes in the Malaysian political landscape have raised questions about the effectiveness of Malaysian media reform plans. This study investigated the journalistic practices employed by Malaysian mainstream and independent media in reporting political parties before and after the 15th general election. Using a quantitative content analysis approach, an integrative framing analysis was conducted on 863 news articles from English, Malay, and Chinese language online newspapers. The findings revealed both significant differences and similarities in the framing practices used by the media outlets. Notably, both mainstream and independent media heavily relied on morality and responsibility frames, while conflict frame was found to have declined significantly in the post-election period. The media also utilised visual frames to address political issues and convey specific narratives. Furthermore, the news tone was found to strengthen the functions of news frames, with the responsibility frame written in a positive tone, and the morality and conflict frames written in a negative tone. This integrative analysis can deepen the understanding of the framing strategies employed by the different types of media and expand existing knowledge by exploring the connections between various framing approaches.